2020
DOI: 10.1130/g48213.1
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Neoproterozoic seawater chemistry from early diagenetic dolomite

Abstract: The pairing of calcium and magnesium isotopes (δ44/40Ca, δ26Mg) has recently emerged as a useful tracer to understand the environmental information preserved in shallow-marine carbonates. Here, we applied a Ca and Mg isotopic framework, along with analyses of carbon and lithium isotopes, to late Tonian dolostones, to infer seawater chemistry across this critical interval of Earth history. We investigated the ca. 735 Ma Coppercap Formation in northwestern Canada, a unit that preserves large shifts in carbonate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…23). Yet, critically, Sr/Ca ratios and δ 44/40 Ca analysis can be used to track the burial offset from seawater in shallow-water carbonates 23,32 (see SI), and there is no evidence for a systematic change in the mode of early marine diagenesis through time that could explain the observed ~ 15‰ increase in mean carbonate δ 7 Li values (or a priori reason to expect such a change). Additionally, we used a suite of commonly employed geochemical filters to constrain primary mineralogy (Sr/Ca, Mg/Ca), track detrital contamination (Al/Ca, Rb/Ca) and diagenetic alteration (Mn/Sr, Pb/Ca) (see SI for further detail).…”
mentioning
confidence: 99%
“…23). Yet, critically, Sr/Ca ratios and δ 44/40 Ca analysis can be used to track the burial offset from seawater in shallow-water carbonates 23,32 (see SI), and there is no evidence for a systematic change in the mode of early marine diagenesis through time that could explain the observed ~ 15‰ increase in mean carbonate δ 7 Li values (or a priori reason to expect such a change). Additionally, we used a suite of commonly employed geochemical filters to constrain primary mineralogy (Sr/Ca, Mg/Ca), track detrital contamination (Al/Ca, Rb/Ca) and diagenetic alteration (Mn/Sr, Pb/Ca) (see SI for further detail).…”
mentioning
confidence: 99%
“…As a consequence, several studies have suggested alternative models for generating such negative δ 13 C values, including (1) short-term transient perturbations to the carbon cycle (e.g., Schrag et al 2002;Rothman et al 2003;Bjerrum and Canfield 2011), (2) carbonate diagenesis (Derry 2010;Knauth and Kennedy 2009) or (3) the formation of authigenic carbonate minerals (Tziperman et al 2011;Schrag et al 2013;Laakso and Schrag 2020). However, these models do not consider the possibility of broadly synchronous shifts in δ 13 C DIC in platform waters (Swart 2008;Ahm et al 2019;Crockford et al 2020), that may differ across individual basins on time-scales >10 5 years, and therefore are unrelated to changes in global DIC -analogous to observations from recent carbonate platforms.…”
Section: The Neoproterozoicmentioning
confidence: 99%
“…from the average ocean value (Bold et al 2020;Crockford et al 2020). Various mechanisms have been proposed to explain the origin of very depleted δ 13 C values in Neoproterozoic platform interior carbonates but, as of yet, no single hypothesis is accepted widely.…”
Section: The Neoproterozoicmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium is a common component in carbonates and its isotopes have been applied to paleoenvironmental and paleographic studies (Crockford et al, 2020;Fantle and Higgins, 2014;Gothmann et al, 2017;Higgins and Schrag, 2012;Li et al, 2015;Liu et al, 2018;Pogge von Strandmann et al, 2014). Moreover, isotopes can provide unique information for mineral dissolution, precipitation, as well as ion exchange between minerals and fluids (e.g., Chanda et al, 2019;Frierdich et al, 2019;Gorski and Fantle, 2017;Liu and Li, 2020;Zhu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%